Abdominal Paracentesis Drainage Does Not Increase Infection in Severe Acute Pancreatitis. Issue 9 (October 2015) - Liu, Liye; Yan, Hongtao; Liu, Weihui; Cui, Jianfeng; Wang, Tao; Dai, Ruiwu; Liang, Hongyin; Luo, Hao; Tang, Lijun
<x xml:space="preserve">Abstract</x> Goals: To demonstrate the relationship between abdominal paracentesis drainage (APD) and infectious complications in moderately severe acute pancreatitis (MSAP) or severe acute pancreatitis (SAP) patients. Background: The effectiveness of APD for SAP was demonstrated in our previous study. However, the relationship between APD and infectious complications has not been fully elucidated. Study: We conducted a prospective cohort study of 255 patients with MSAP or SAP. The patients were divided into 2 groups: patients with acute pancreatitis who underwent APD (group 1) and patients with acute pancreatitis who did not undergo APD (group 2). Four types of infectious complications were evaluated: bacteremia, infected necrosis, pneumonia, and sepsis. The pathogens responsible for infectious complications were analyzed. The need for percutaneous catheter drainage and mortality were also compared between the 2 groups. Results: A total of 255 patients were included with analogous baseline features. The rate of overall infectious complications in group 1 was 38.1%, which was lower than that in group 2 (52.7%, P=0.019). This difference was mainly based on infected necrosis (12.7% and 23.3% in groups 1 and 2, respectively, P=0.034). The microbial spectrum was similar in the 2 groups. Percutaneous catheter drainage was used less frequent in group 1 (18.3%) than in group 2 (31.8%, P=0.014). The infection-related mortality in groups 1 and 2 was 6.5% and 8.5%, respectively, and there was no significant difference (P=0.457). Conclusion: Our results indicate that APD did not increase the infectious complications and infection-related mortality compared with the strategy without APD in patients with MSAP or SAP.